(untitled) (Switzerland, 1948)
This book introduce the facts about Switzerland and her Natinal economy. Switzerland's economic relations with world markets. What Switzerland produc. The tourist trade and ecducation.
Keywords: Switzerland,Thụy sĩ; Eonomic conditions,Điều kiện kinh tế